Integrasi Nilai Budaya Tradisi 1 Suro Petilasan Sri Aji Joyoboyo dalam Bimbingan Konseling untuk Meningkatkan Self-Awareness - Muh Madhani Rahmatullah; Dealova Savara; Grace Luvita Artika Sinambela; Rismanda Dwi Saputra; Nael Nahdiyah Azzahra (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2026)
The purpose of this study was to investigate how the cultural values of the 1 Suro Ceremony tradition at the Sri Aji Jayabaya Petilasan can be integrated into guidance and counseling services to increase self-awareness. This study used a qualitative descriptive method. Data were collected through observations, interviews, and documentation involving the caretaker and the surrounding community. The findings showed that the tradition contains important values such as spirituality, self-reflection, respect for ancestors, social togetherness, and mutual cooperation. Activities such as collective prayers and reflection were believed to help individuals understand themselves and build harmonious relationships with God, others, and the environment. These cultural values can be applied in guidance and counseling services as a form of local wisdom–based learning. The study is expected to contribute to the development of counseling services that support character building and improve students’ self-awareness in schools.